Mobile photon counting detector CT with multi material decomposition methods for neuroimaging of patients in intensive care unit - Su-Jin Park; Kwanhee Han; Junyoung Park; Jonghwan Min; Dufan Wu; Doil Kim; Kyutae Kang; Duhgoon Lee; Rajiv Gupta; Jinwook Jung (Scientific Reports)
Abstract The photon-counting detector computed tomography (PCD-CT) is a promising new technology that provides more spectral information in medical imaging. PCD-CT enables bedside imaging in the neuro intensive care unit (neuro ICU) for patients with life-threatening conditions such as brain hemorrhage and ischemic stroke. The primary purpose of this study is to evaluate a multi-material decomposition algorithm available on PCD-CT, dubbed MD Plus, to differentiate between contrast agent and hemorrhage in hyperdense lesions. A certified multi-energy phantom was used to validate its performance with various x-ray exposure conditions and locations of contrast agent. The results from the quantitative analysis of multi-energy phantoms and the clinical cases of patients in the ICU demonstrated that MD Plus can accurately differentiate between the contrast agent and the hemorrhage. The extended MD Plus algorithm, including virtual non-contrast (VNC) and bone removal, was also validated for various clinical applications.